The Effect Of Composition Variation On The Functional Groups Of Coconut Husk Ash Silica Nanocomposites With Titanium Dioxide - Mardiana, Mardiana; Ratnawulan, Ratnawulan (Journal of Experimental and Applied Physics, 2024)
Studie has been performed with the title Effect of Composition Versions on Useful Corporations of Coconut Coir Ash Silica Nanocomposites with Titanium Dioxide. This study goals to determine the traits of silica gel from the processing of coconut husk ash thermodiffcation TiO2 in phrases of useful groups variations in silica composition with titanium dioxide, particularly 3.5: 1.5 and 4: 1 (grams). The synthesis of silica gel from coconut husk ash become finished the use of the gel sol method. FTIR (Fourier Transform Infrared) characterization effects show the achievement of TiO2 changed silica gel and silica gel synthesis proven with the aid of the absorption of Si-O-Si and Si-OH in silica gel and Ti-O-Ti absorption in TiO2 changed silica gel. Based on the FTIR spectrum, it was obtained that during all samples an ordinary practical group of TiO2 seemed, specifically Ti-O at an absorption peak of about 500-600 cm-1 O-H vibrational bond stretching and O-H bending at an absorption height of 1500 - 3500 cm-1 Appeared in all samples indicating the presence of water molecules. In addition, Ti-O-Si vibrational bonding at absorption peaks of 700 - 1000 cm-1 regarded on all samples indicating the archiement of the composite synthesis method TiO2 - SiO2.